Effects of Periodic Markets on Job Creation, Socioeconomic Growth and Sustainable Development (Global Journal of Human-Social Science, 2019)
The study focuses on the effects of periodic markets on socio-economic development of Giwa Local Government Area of Kaduna State. Purposive sampling and Random sampling technique were used to sample four periodic markets and 437 respondents in the study area. Data were collected using questionnaire focusing on participants from the four different periodic markets across Giwa Local Government Area. The data was analysed using both descriptive and multiple regression analysis. The study revealed that periodic markets have significant effect on the socio-economic development of the study area as confirmed by the regression analysis which were significant at 5% level through increase in trader's income (0.000), with 24% of the traders earning above N 30,000 monthly, and creation of job opportunities (0.000) like head loaders, carriers, shoe makers road transport workers, grain mill, welding, telecommunication business etc,. It is concluded that, periodic markets have tremendous effects on the socioeconomic development of Giwa Local Government Area. It is recommended that, there should be establishment of financial institutions in the study area which will help traders to have access to loans to enable them expand their business to earn more income.
Keywords: periodic markets; job creation; socio-economic development